Boost faculty morale by recognizing excellent service. Issue 10 (18th May 2021) - Sutton, Halley
Abstract : John Geer has been at Vanderbilt University for 26 years. "I'm kind of an accidental administrator — it's not something I ever thought I'd do, " Geer said. But when then‐Chancellor Nick Zeppos asked Geer to co‐lead the university strategic plan, telling Geer he wanted him to experience the university from Zeppos' perspective for a year, Geer agreed.